Household Division and Rural Economic Growth - Foster, Andrew D.; Rosenzweig, Mark R. (Review of Economic Studies, 2002)
Andrew D. Foster, Mark R. Rosenzweig; Household Division and Rural Economic Growth, The Review of Economic Studies, Volume 69, Issue 4, 1 October 2002, Pages 83